A comparative analysis of housing institutions: Malawi Housing Corporation and Johannesburg Social Housing Company and their contribution to social integration and affordable housing sector - Khunga, Lusubilo Mwakalagho (My University, 2015)
The research is a comparison of two state-owned housing institutions namely, the Johannesburg Social Housing Company and the Malawi Housing Corporation and how they are contributing to affordable housing and social integration in the housing sector. It uses a qualitative approach. Objectives of the research were achieved through obtaining primary written data that was collected through document reviews from the relevant organisations and interviews. The interviews were supported through the use of secondary materials. The research strategy was comparative in nature and content analysis was used to analyse the data obtained. The study showed that integration ensures that housing institutions provide housing without segregation and discrimination bias while affordability is a mechanism for housing provision to households whose housing needs are not met by the housing market. The research results portrayed that JOSHCO’s housing affordability is more meaningful than MHC’s because JOSHCO offers housing within the social economic opportunities in the inner city while MHC provides housing estates outside the inner city. It also showed that both institutions consider issues of income, gender, race and disability in their housing projects and programmes to ensure that integration occurs.
A research report on a study presented to the School of Architecture and Planning, Faculty of Engineering and the Built Environment, University of the Witwatersrand
Keywords: Housing--Africa; City planning--Africa; Urbanization--Africa